Kebocoran Data dan Tanggung Jawab Hukum Korporasi Digital: Menggagas Rezim Akuntabilitas Mutlak dalam Ekosistem Ekonomi Digital Indonesia - Gilang Rizki Aji Putra (UIN Jakarta, 2022)
This article examines corporate legal liability for personal data breaches in Indonesia’s digital business sector under Law No. 27/2022 on Personal Data Protection (PDP Law). Using normative legal research with statutory, conceptual, and comparative approaches, the study finds weaknesses in proof mechanisms, sanctions, and collective compensation systems. Current regulations rely heavily on fault-based liability, burdening victims despite the massive and asymmetrical nature of data breaches. Cases in digital finance and e-commerce reveal weak corporate accountability and limited victim recovery. The article recommends adopting strict liability, stronger supervisory authority, and accessible class action mechanisms. Keywords: Data Breach, Corporate Liability, Strict Liability, PDP Law, Collective Compensation.